Memahami Implementasi Manfaat Waktu pada Aktivitas Sehari-Hari dalam Surat Al-‘Ashr Menurut Tafsir Al-Mishbah - Muhammad Hasbi Nurchoironi; Ahmad Nurrohim (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2025)
The purpose of this study is to understand the implementation of the benefits of time in daily activities in the letter al-'ashr according to the interpretation of al-mishbah. This study uses the library research method in obtaining data. The approach taken by the author is an interpretive approach and descriptive-analytical method analysis. Descriptive-analytical method analysis is an analysis that describes the thoughts of the Al-Mishbah interpretation figure, namely M. Quraish Shihab regarding understanding the implementation of the benefits of time in the letter al-'ashr which is analyzed critically, then looking for the roots of M. Quraish Shihab's thoughts. The results of this study are that Quraish Shihab's interpretation of the letter al-'ashr provides a deep understanding of the importance of time, how to use it, and how to avoid losses caused by wasting it.